A study on the awareness level of contractor towards sustainable construction / Norfazlina Ramli - Ramli, Norfazlina (Faculty of Architecture, Planning and Surveying, 2008)
Sustainable is a way for the building industry to move towards achieving sustainable development, taking account to environmental and social to different priorities. This research presents the level of awareness among contractors area Selangor and Kuala Lumpur. So the study in the implementation on sustainable principles is encouraged to get their response and to know the level of knowledge about the level of awareness in sustainable construction among contractor. Data was collected by questionnaire. Result from my analysis that can be conclude that contractors are lack of awareness about Sustainable Construction issue. Only contractor upper grade just understand about sustainable construction different with the contractor lower grade. Sustainable construction seeks for proper management of all aspect of building design, construction, operation, and use. The principle in sustainable construction should be implement by contractors for ensure that for a better living. Contractors should have positive support the efforts towards providing environmental friendly.